2021
DOI: 10.3389/fcell.2021.688238
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-Specific RIP2 Overexpression Exacerbated Pathologic Remodeling and Contributed to Spontaneous Cardiac Hypertrophy

Abstract: This study aimed to investigate the role and mechanisms of Receptor interacting protein kinase 2 (RIP2) in pressure overload-induced cardiac remodeling. Human failing or healthy donor hearts were collected for detecting RIP2 expression. RIP2 cardiomyocyte-specific overexpression, RIP2 global knockout, or wild-type mice were subjected to sham or aortic banding (AB) surgery to establish pressure overload-induced cardiac remodeling in vivo. Phenylephrine (PE)-treated neonatal rat cardiomyocytes (NRCMs) were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…RIP2 overexpression aggravates myocardial infarction-related cardiac remodeling, and its mechanism is related to the activation of p38 phosphorylation (19). Previously (60), it was demonstrated that the expression of RIP2 was significantly increased in cardiac cells in patients with heart failure, mice with aortic banding surgery-induced pressure overload and phenylephrine-treated cardiomyocytes in vitro. Notably, RIP2 overexpression aggravates pressure overload-induced cardiac remodeling (60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RIP2 overexpression aggravates myocardial infarction-related cardiac remodeling, and its mechanism is related to the activation of p38 phosphorylation (19). Previously (60), it was demonstrated that the expression of RIP2 was significantly increased in cardiac cells in patients with heart failure, mice with aortic banding surgery-induced pressure overload and phenylephrine-treated cardiomyocytes in vitro. Notably, RIP2 overexpression aggravates pressure overload-induced cardiac remodeling (60).…”
Section: Discussionmentioning
confidence: 99%
“…Previously (60), it was demonstrated that the expression of RIP2 was significantly increased in cardiac cells in patients with heart failure, mice with aortic banding surgery-induced pressure overload and phenylephrine-treated cardiomyocytes in vitro. Notably, RIP2 overexpression aggravates pressure overload-induced cardiac remodeling (60). The expression and function of RIP2 in CKD-associated cardiac injury have not yet been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…After 90 min of differential attachment culture, the CFs were attached to the bottom of culture dish while the NRCMs existed in the culture medium. The NRCMs were counted and cultured in a 6-well plate with cell density of 5 × 10 6 and treated with AngII (1 μM) or PBS in the presence of different concentrations of CTS (0, 3, 6, and 12 μM) for 12 h. The CFs were passaged to the second generation and then were counted and cultured in a 6-well plate with a cell density of 2 × 10 6 and treated with TGF-β (10 μM) or PBS in the presence of different concentrations of CTS (0, 3, 6, and 12 μM) for 12 h. The dose of AngII (1 μM) and TGF-β(10 μM) was performed as previously described [20,21]. Western blot was performed to assess the effect of CTS.…”
Section: Assessing Cardiac Functionmentioning
confidence: 99%